Effects of exercise and lifestyle intervention on oxidative stress in chronic kidney disease. (4th May 2017) - Small, David M.; Beetham, Kassia S.; Howden, Erin J.; Briskey, David R.; Johnson, David W.; Isbel, Nicole M.; Gobe, Glenda C.; Coombes, Jeff S.
ABSTRACT: Objectives: Determine the effects of a 12-month exercise and lifestyle intervention program on changes in plasma biomarkers of oxidative stress in pre-dialysis chronic kidney disease (CKD) patients. Methods: A total of 136 stage 3–4 CKD patients were randomized to receive standard nephrological care with ( N = 72) or without ( N = 64) a lifestyle and exercise intervention for 12 months. Plasma total F2 -isoprostanes (IsoP), glutathione peroxidase (GPX) activity, total antioxidant capacity (TAC), anthropometric and biochemical data were collected at baseline and at 12 months. Results: There were no significant differences between groups at baseline. There were no significant differences in changes for standard care and lifestyle intervention, respectively, in IsoP ( p = 0.88), GPX ( p = 0.87), or TAC ( p = 0.56). Patients identified as having high IsoP at baseline (>250 pg/mL) had a greater decrease in IsoP with lifestyle intervention compared to standard care; however, the difference was not statistically significant ( p = 0.06). There was no difference in the change in kidney function (eGFR) between standard care and lifestyle intervention ( p = 0.33). Discussion: Exercise and lifestyle modification in stage 3–4 CKD did not produce changes in systemic biomarkers of oxidative stress over a 12-month period, but patients with high IsoP may benefit most from the addition of intervention to standard care.